Knockdown of Long Non-Coding RNA UCA1 Increases the Tamoxifen Sensitivity of Breast Cancer Cells through Inhibition of Wnt/β-Catenin Pathway. - Hongying Liu; Gang Wang; Lili Yang; Jianjun Qu; Zhihui Yang; Xiangyu Zhou (PLoS ONE, 2016)
Acquired resistance to tamoxifen remains a major obstacle in breast cancer (BC) treatment, since the underlying mechanism has not been fully elucidated. The long non-coding RNA (lncRNA) urothelial carcinoma-associated 1 (UCA1) has been recently shown to be dysregulated and plays important roles in progression of breast cancer. In the present study, we aimed to investigate the biological role and clinical significance of UCA1 in BC drug resistance. Hence, we used quantitative PCR assay to evaluate the UCA1 expression in tissues from patients with BC as well as established tamoxifen-resistant BC cell lines in vitro. We tested the viability, invasive ability and apoptosis rate in MCF-7 and T47D cells using MTT assay, transwell assay and flow cytometry assay, respectively. The influence of UCA1 on tumorigenesis was monitored by in vivo mice xenograft model. The activation of Wnt/β-catenin signaling pathway was evaluated by immunofluorescence assay, western blot assay and luciferase reporter assay, respectively. We found that the expression of UCA1 positively correlated with the pathological grade and mortality of breast cancer patients, moreover, expressions of UCA1 was increased significantly in the tamoxifen-resistant cell lines compared with the wild type parental cells. Ectopic expression of UCA1 promoted cell survival and resistance to tamoxifen treatment, whereas inhibition of UCA1 enhanced tamoxifen sensitivity of BC cells and induced more apoptotic cells. In addition, tamoxifen-resistant cells exhibited increased Wnt signaling activation as measured by the TOP/FOP Wnt luciferase reporter assay and β-catenin protein level compared with parental MCF-7 and T47D cells, respectively. In line with these data, UCA1 depletion attenuated the activity of Wnt/β-catenin pathway activation and the tumorigenicity of the tamoxifen-resistant BC cells. Taken together, our data highlights the pivotal role of UCA1-Wnt/β-catenin signaling pathway in the tamoxifen resistance in breast cancer, which could be targeted to improve the effectiveness and efficacy of tamoxifen treatment in breast cancer.